Hubungan Pengetahuan dan Dukungan Suami dengan Penggunaan KB Pasca Persalinan : Scoping Review - Era Yasinta; Machfudloh, Machfudloh (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
The achievement of postpartum family planning in Indonesia in 2022 is around 52.3% of the target of 70%. This shows that the use of postpartum family planning has not reached the desired target. Objective: This article aims to determine the relationship between knowledge and husband's support with the use of postpartum family planning. Method: The method used is the scoping review method. Literature search using 3 databases, namely ScienceDirect, PubMed, Willey Online Library, and one search engine; Google Scholar. Articles were selected using inclusion criteria, namely original articles, using Indonesian and English, published in the last 5 years (2020-2025). Results: The results of the review found data related to knowledge of postpartum family planning, husband's support and the relationship between knowledge and husband's support with the choice of postpartum family planning. From the review of 10 articles, it was found that 83.6% of respondents had good knowledge and used postpartum family planning and respondents with less knowledge (16.4%). Respondents who received support from their husbands (52.8%) and those who did not receive support from their husbands were (47.2%). Efforts to increase maternal knowledge by providing information, clear and correct motivation regarding postpartum family planning and encouraging husbands' participation in family planning programs.